2018
DOI: 10.1371/journal.pone.0208092
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of outbreaks with Methicillin-resistant Staphylococcus aureus (MRSA) in Dutch long-term care facilities (LTCF)

Abstract: ObjectivesHighly resistant microorganisms (HRMOs) are of high concern worldwide and are becoming increasingly less susceptible for antibiotics. To study the cost effectiveness of infection prevention measures in long-term care, it is essential to first fully understand the impact of HRMOs. The objective of this study is to identify the costs associated with outbreaks caused by Methicillin-resistant Staphylococcus aureus (MRSA) in Dutch long-term care facilities (LTCF).MethodsAfter an outbreak of MRSA, Dutch LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Using 2021 as a base year for comparing our cost estimates with other studies, we found our estimated extra patient cost of AMR was less compared with another study conducted in a hospital in Connecticut, USA, which shows that the excess expense per patient due to AMR was equivalent to US$1871 [ 23 ]. Furthermore, an increasing number of studies, mainly conducted in Europe and the US, report a higher patient cost of AMR with variation in excess cost depending on the bacteraemia type, sample size, study perspective, and location [ 21 , 46 , 51 53 ]. Nonetheless, we are cautious in comparing our estimated costs with available studies conducted in Europe and the US due to complete differences in socioeconomic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Using 2021 as a base year for comparing our cost estimates with other studies, we found our estimated extra patient cost of AMR was less compared with another study conducted in a hospital in Connecticut, USA, which shows that the excess expense per patient due to AMR was equivalent to US$1871 [ 23 ]. Furthermore, an increasing number of studies, mainly conducted in Europe and the US, report a higher patient cost of AMR with variation in excess cost depending on the bacteraemia type, sample size, study perspective, and location [ 21 , 46 , 51 53 ]. Nonetheless, we are cautious in comparing our estimated costs with available studies conducted in Europe and the US due to complete differences in socioeconomic circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Probability of chronic COVID taken from the fatigue estimate given in [ 33 ] QALY loss, death Net present value of total QALYs lost from [ 32 ], modified with Canadian population norms and SDs Incremental cost, hospitalisation and ICU admission Per diem median $1391.80, 90th percentile $1852.52 Gamma distribution: α = 18.5, β = 0.01 Alberta Health Interactive Health Data Application, CMG+ 2018 Grouper 133, Infectious/Parasitic Disease of Respiratory System [ 34 ]. Inflation adjusted from 2018 to 2020 using Canada All-Item inflation [ 35 ] Incremental cost, LTC case Per diem mean $337.65, SD $548.14 Gamma distribution: α = 0.8547, β = 0.0025 Cost from [ 36 ] converted to CAD using average 2015 exchange rate, inflation adjusted from 2015 to 2020 using Canada All-Item inflation [ 35 ] Incremental cost, chronic COVID Annual cost of $10,020, with probability 34.8% Beta distribution for probability: α = 2.410903, β = 4.516979 Weighted expected annual cost for common chronic conditions associated with chronic COVID. See the ESM for details.…”
Section: Methodsmentioning
confidence: 99%
“…It is found colonizing the nostrils of approximately 20%-30% of the adult population (Mulcahy and McLoughlin 2016;Krismer et al 2017), and current studies have also shown the occurrence of S. aureus and methicillin-resistant S. aureus (MRSA) in healthy children and youth (Hussein et al 2015;Kateete et al 2019). MRSA is associated with a variety of infections that cause high morbidity, mortality, and healthcare costs, such as hospitalization in the intensive care unit (ICU), generating considerable socioeconomic impacts (Chatterjee et al 2018;van Rijt et al 2018) Fouda et al (2016) corroborate this finding, in which 70% of healthcare professionals were stable MRSA carriers. To address this issue, systematic surveillance and research efforts are required (Rasigade et al 2014).…”
Section: Introductionmentioning
confidence: 99%